Ameliorative Effects of Aspergillus awamori against the Initiation of Hepatocarcinogenesis Induced by Diethylnitrosamine in a Rat Model: Regulation of Cyp19 and p53 Gene Expression - Doaa H. Assar; Abd-Allah A. Mokhbatly; Emad W. Ghazy; Amany E. Ragab; Samah Abou Asa; Walied Abdo; Zizy I. Elbialy; Nora Elbialy Mohamed; Ali H. El-Far (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is the most common cancer in humans. Despite advances in its treatment, liver cancer remains one of the most difficult cancers to treat. This study aimed to investigate the ameliorative action and potential mechanism of Aspergillus awamori (ASP) administration against the initiation process of liver carcinogenesis induced by diethylnitrosamine (DEN) in male Wistar rats. Seventy-two male rats were divided equally into eight groups as follows, Group 1: untreated control; Group 2: DEN (200 mg/kg bw) intra-peritoneally for the initiation of HCC; Groups 3-5: DEN + ASP at a dose of 1, 0.5, and 0.25 mg/kg bw and groups 6-8: ASP at a dose of 1, 0.5, and 0.25 mg/kg bw. Supplementation of A. awamori significantly lightened the adverse impacts induced by DEN via restoring the leukogram to normal, lowering the elevated serum aspartate aminotransferase (AST), alanine transaminase (ALT), and γ-glutamyl transferase (GGT), and alkaline phosphatase (ALP). Furthermore, it enhanced the hepatic antioxidant capacity through increasing the reduced glutathione (GSH) level and catalase (CAT) activity with a marked reduction in malondialdehyde (MDA) level. In addition, it decreased the positive GST-P foci. Likewise, a significant alteration of DEN-associated hepatocarcinogenesis occurred through inhibiting cytochrome P450 (Cyp19) and activating p53 gene expression. In conclusion, supplementation of A. awamori counteracts the negative effects of DEN, inhibits the early development of GST-P-positive foci and could be used as a new alternative strategy for its chemo-preventive effect in liver cancer. To the best of our knowledge, the present study is the first to report the hepato-protective effect of A. awamori in induced hepatocarcinogenesis.